A Novel Method of Intraosseous Infusion of Adenosine for the Treatment of Supraventricular Tachycardia in an Infant. Issue 1 (January 2017) - Helleman, Krista; Kirpalani, Amrit; Lim, Rodrick
Abstract : Abstract: Supraventricular tachycardia is a common arrhythmia faced by emergency physicians in the pediatric population. In most cases, antecubital intravenous access can be established, and adenosine can be administered in a rapid and timely fashion. The role and administration of intraosseous adenosine are poorly established. We describe a case where the administration of adenosine was successful via a mixed method administration.